A Sociocognitive Perspective on Assessing EL Students in the Age of Common Core and Next Generation Science Standards. Issue 3 (22nd August 2014) - Mislevy, Robert J.; Durán, Richard P.
<x xml:space="preserve">Abstract</x> Subject‐area standards such as Common Core State Standards for Language Arts and Mathematics and Next Generation Science Standards offer deeper, richer views of subject‐area proficiency. In science, they underscore doing things with facts and concepts, such as explaining, planning, and investigating—activities that are intertwined with language, with specialized structures and functions of academic English. This article explores the implications of a sociocognitive view of learning for assessment based on these standards, focusing on English learners (ELs). The authors describe how ELs and native English speakers alike develop subject‐area and language resources jointly through activities, and how teachers use local knowledge to scaffold this development for students from diverse cultures and varying English experience. They then describe concomitant assessment strategies. The grounding of the standards in learning progressions enables the design of tasks which, while complex, challenge particular aspects of capability at targeted levels. A strategy can be used to craft tasks that are at once consistent with the standards but targeted to students with differing profiles of capabilities. This design strategy is well suited to contextualized formative assessment in local contexts such as classrooms. It supports design for large‐scale assessment as well, although rich and complex tasks that are not matched to students' language and subject‐area profiles face the low generalizability that plagued performance assessments in the 1980s. We consider ways that assessment design and tailored adaption can ameliorate some of the difficulties.